Perancangan Sistem Manajemen Perusahaan Pengembang Perumahan CV. ABC - Yuniaristanto -; Azizah Aisyati; Wisdania Rusdianasito (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
CV. ABC is a property developer which hasn’t had a clear system in its business processes and Standard Operational Procedures (SOP) so that causes the company’s jobs become less regular. By this situation, the goals of this research are to design the organizational structure, business process and the SOP for the CV. ABC. The system design is conducted by competitive benchmarking toward a competitor namely CV. Catur Tunggal Sentosa (CTS). Through the competitive benchmarking, it will be designed organizational structure, bussiness process and SOP for CV. ABC. The bussiness process design uses Business Process Improvement (BPI) method which reform steps to improve the earlier business processes. Based on the proposed business process, it is described more detail in SOP to understand and comprehend the job activities in this company. The results of this research are organizational structure, business process and SOP for CV. ABC. The new organizational structure is the line organization structure with the jobs specification are more focus. Those jobs specification are marketing, administration/finance and project. SOP design contains 11 SOP such as site selection, land acquisition, project planning, licensing, promotion, sales by loan, sales by cash, construction bidding, construction control, home handover, and complaints.